British periodicals collection : I & II (2006)
British Periodicals consists of two separate collections, British Periodicals Collection I and British Periodicals Collection II. British Periodicals Collection I consists of more than 160 journals that comprise the UMI microfilm collection Early British Periodicals, the equivalent of 5,238 printed volumes containing approximately 3.1 million pages. Topics covered include literature, philosophy, history, science, the fine arts and the social sciences. British Periodicals Collection II consists of more than 300 journals from the UMI microfilm collections English Literary Periodicals and British Periodicals in the Creative Arts together with additional titles, amounting to almost 3 million pages. Topics covered include literature, music, art, drama, archaeology and architecture.